Structural insights into the enzymatic breakdown of azomycin-derived antibiotics by 2-nitroimdazole hydrolase (NnhA) - F. Hafna Ahmed; Jian-Wei Liu; Santana Royan; Andrew C. Warden; Lygie Esquirol; Gunjan Pandey; Janet Newman; Colin Scott; Thomas S. Peat (Communications Biology)
Abstract The antibiotic 2-nitroimidazole (2NI) or azomycin, used for treating drug-resistant tuberculosis and imaging tumor hypoxia, requires activation by bacterial nitroreductases for its antibiotic and cytotoxic effect. Mycobacterium sp. JS330 produces 2-nitroimidazole nitrohydrolase (NnhA) that circumvents 2NI activation, conferring 2NI resistance by hydrolysing it to nitrite and imidazol-2-one (IM2O) instead. This study elucidates NnhA’s structure, catalytic mechanism, and evolutionary background within the guanidino-group modifying enzyme (GME) superfamily, aided by a more soluble protein variant engineered through directed evolution. Despite low sequence similarity and limited occurrence in a few soil-dwelling mycobacteria and Actinomycetota, NnhA maintains the α/β propeller fold characteristic of GME superfamily enzymes and forms an unusual hexameric ring structure formed by a trimer of domain-swapped dimers. The similarity of its active site to arginine deiminases (ADIs) and human dimethylarginine dimethylaminohydrolases (DDAHs), along with molecular dynamics simulations, suggests NnhA’s catalytic mechanism resembles the hydrolysis reactions of these related enzymes.